Effects of Land Use/Land Cover Changes on Selected Soil Physical and Chemical Properties in Shenkolla Watershed, South Central Ethiopia - Belayneh Bufebo; Eyasu Elias (Advances in Agriculture)
Land use change from natural ecosystems to managed agroecosystems is one of the main causes of soil fertility decline. Severe soil erosion caused by agricultural expansion and poor management worsened soil nutrient depletion in cultivated outfields (crop lands). This study was conducted to examine the effects of land use and land cover changes (LU/LC) on selected soil physicochemical properties in the Shenkolla watershed. A total of 40 top soil samples at 0–20 cm depth were collected from four land use/land cover types (forest land, grazing land, cultivated outfield, and cultivated homestead garden fields). The analysis of variance (ANOVA) was applied to determine differences in soil parameters among land use types. Treatment means comparison was determined using the least significant difference (LSD) at 0.05 level of significances. The result indicated that there were significant P<0.05 differences among the four LU/LC types for soil characteristics. For most parameters evaluated, the most favorable soil properties were observed in the forest land, followed by homestead garden fields, while the least favorable soil properties were found in intensively cultivated outfields. Increase in the extent of cultivated land at the expense of forest cover associated with poor management has promoted significant loss of soil quality in intensively cultivated outfields. Reducing the land cover conversion and adopting proper management practices of the soil commonly used in homestead garden fields are very crucial in order to improve soil fertility in intensively cultivated outfields.